5-Bromo-1H-indole-3-carbaldehyde 2-thienoyl-hydrazone - Ali, H.M.; Ng, S.W.; Zain, Sharifuddin Md; Basirun, Wan Jefrey; Lajis, N.; Halim, S.N.A. (International Union of Crystallography, 2005)
In the title molecule, C14H10BrN3OS, the indole moiety is twisted by 36.0(2)° with respect to the disordered thienyl group and the nitrogen-bound H atoms interact with the amide O atoms of symmetry-related molecules, resulting in an N-H⋯O hydrogen-bonded layer structure. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.